The Development of PISA Questions and Activities Using Social Distancing Context During Pandemic - Risda Intan Sistyawati; Zulkardi Zulkardi; Hapizah Hapizah (Universitas Sriwijaya, 2022)
The emergence of this research is caused by the low mathematical literacy of students in Indonesia. This study aims to obtain valid, practical, and have potential effects of PISA type questions and activities using social distancing context during pandemic. This study is design research with the type of development studies which consist of two main stages, including preliminary design and formative evaluation. This study took a special research subject for grade IX junior high school students aged 14-16 years in the city of Palembang. Analysis of the results of this study was carried out qualitatively based on data in the field obtained in the form of interviews, photos and videos to see student activities in working on questions and activities. From this study, the results obtained include one type of activity and one evaluation question of the results of developing PISA type questions and activities with the context of social distancing during a pandemic that grade IX students can use to develop their mathematics literacy skills. In conclusion, PISA type questions and activities with the context of social distancing during the pandemic can be used for the learning process in the classroom to improve students' mathematical literacy.